Sensitivity of Propolis Solutions on Aeromonas hydrophila Bacteria - Bako, Surandha; Lukistyowati, Iesje; Riauwaty, Morina (Jurnal Perikanan dan Kelautan, 2019)
This research was conducted in November 2016 - May 2017 in Parasites and Fish Disease Laboratory of Marine and Fisheries Faculty University of Riau. The purpose of this research is to know the dosage and the ability of propolis solution in inhibiting the growth of Aeromonas hydrophila bacteria and the safe dosage used for common catfish with LD50tested by immersion. The used methodwere experiment and sensitivity test using Kirby Baeur Disk Diffussion method from dose 100% to 0.5% and repeated 3 times. The used dosage in Minimum  Inhibitory Concentration (MIC) tests were 9%, 8%, 7%, 6% and 5%. While LD50 toxicity test using common catfish (Clarias sp) with dose 5%, 6% and 7% for 24 hours. The results showed that the propolis solution was able to inhibit the growth of A. hydrophila bacteria with the smallest dosage of 0.9% equal to 90 ppm, with the diameter inhibitory average zone of 6.78 mm, the safest dose of MIC was present at 6% doses equivalent to 600 ppm with 8,15 mm inhibition zone width  and inhibited bacterial growth  A. hydrophila with an average number of colonies as much as 278 Cells/mL. LD50toxicity test using MIC dosage results showed that no fish mortality for 24 hours.